2020
DOI: 10.1039/d0sm01024c
|View full text |Cite
|
Sign up to set email alerts
|

Spinning elastic beads: a route for simultaneous measurements of the shear modulus and the interfacial energy of soft materials

Abstract: Large deformations of soft elastic beads spinning at high angular velocity in a denser background fluid are investigated theoretically, numerically, and experimentally using millimeter-size polyacrylamide hydrogel particles introduced in a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This means that the relationship between the applied external stress and the deformation of the sensor involves both the shear stress modulus µ d and the surface tension γ c . For small deformations, it has been shown that one can take into account this elasto-capillary contribution by introducing an effective elastic constant µ e (Carbonaro et al, 2020): with K is a dimensionless constant of order unity. We thus performed an in situ calibration on a sensor embedded in a tissue, in order to directly measure µ e .…”
Section: Resultsmentioning
confidence: 99%
“…This means that the relationship between the applied external stress and the deformation of the sensor involves both the shear stress modulus µ d and the surface tension γ c . For small deformations, it has been shown that one can take into account this elasto-capillary contribution by introducing an effective elastic constant µ e (Carbonaro et al, 2020): with K is a dimensionless constant of order unity. We thus performed an in situ calibration on a sensor embedded in a tissue, in order to directly measure µ e .…”
Section: Resultsmentioning
confidence: 99%
“…tension γc. For small deformations, it has been shown that one can take into account this elasto-capillary contribution by introducing an effective elastic constant µe (Carbonaro et al, 2020):…”
Section: In Situ Calibration In Aggregatesmentioning
confidence: 99%
“…The dominant approach to tackle this fundamental question consists in investigating surface elastic properties. 12,[15][16][17][18] For instance, surface topography measurements of a stretched patterned silicone gel revealed an elastic surface, where surface stresses increase with surface deformations. 15 This result hints towards a role of the crosslinked polymeric network in the surface constitutive behavior of silicone gels.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, deformation measures of a spinning hydrogel bead evidenced constant surface stresses, independent of surface deformations, akin to the solvent surface tension. 18 In its simplest form, the most common description for the surface mechanics of soft solids relates surface stresses r s (in N m À1 ) to surface strains e s and free energy W s (in J m À2 or N m À1 ),…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation